Kajian Yuridis Arbitrase Sebagai Suatu Alternatif Dalam Penyelesaian Sengketa Bisnis Di Luar Pengadilan - Nadya Iswari Mannu Radha; Aryo Fadlian (Peneliti.net, 2022)
Inheritance Business is an activity or agreement of goods and services transactions conducted by two or more parties. In running the business, there are often business problems that cause conflicts or disputes.Business disputes usually occur due to misunderstandings between the parties when conducting the business. Business disputes are also often referred to as trade disputes or commercial disputes. A business dispute is a situation where there is a party that feelsharmed by the other party, which then one of theaggrieved parties conveys dissatisfaction to the party. Business disputes can impact the business productivity of the two parties. If the problem of the dispute, increasingly complicated and no solution point found.So one way is through the settlement of disputes outside the court or called alternative dispute resolution. Thealternative structure of the dispute is basically a form ofout-of-court dispute resolution based on the agreement of the parties to the dispute. Alternative dispute resolution is usually voluntary, or there is no compulsion in the resolution of such disputes